Ukraińcy o własnych błędach w polszczyźnie. Przykład statystycznej analizy danych w glottodydaktycznych badaniach eksploracyjnych - Izdebska-Długosz, Dominika (Przegląd Wschodnioeuropejski, 2018)
In the article the results of survey research on the assessment of errors made in Polish by Ukrainians and Poles, as stated by Ukrainian students learning Polish as a foreign language, are shown. This research was a part of twofold research in which students from Poland participated as well, assessing the character and importance of linguistic errors made by foreigners and native speakers of Polish. At first. the results were shown by means of traditionally counting up the number of particular responses. Nonetheless, the information about how much and what kind of additional data could be gained thanks to elements of statistical analysis of data conducted on the same survey is shown in this paper. The results may convince one that statistical analysis of pilot or exploratory nature is worth conducting even with a small research sample, as it allows for highlighting particular problems which should be taken into account while preparing research tools for proper research.